Understanding of calcium signaling pathway mediated by calmodulin and related proteins in Neurospora crassa - Laxmi, Vijya (My University, 2016)
In this study, I investigated the cellular functions of calmodulin (CaM) and related calcium (Ca2+) signaling proteins in Neurospora crassa. The CaM in N. crassa is essential for viability, therefore, I studied its function using the CaM antagonists, trifluoperazine (TFP) and chlorpromazine (CPZ). I found that the addition of CaM antagonists inhibit growth, hyphae branching, and sexual development in N. crassa. I also studied Ca2+ -ATPases that are important targets of CaM and maintain Ca2+ homeostasis in cells. Double mutant of the Ca2+ -ATPases, encoded by trm-9 and nca-2, exhibited a growth defect, less pigmentation, reduced survival in Ca2+ stress and induced heat shock temperature in N. crassa. In addition, I isolated mutants of the calmodulin gene (cmd) using repeat-induced point mutation to identify the important amino acid residues. One of the eight cmdRIP mutants isolated, the ?pan-2::Ptcu-1::cmd RIP(26); mat A strain possess missense mutations, showed a decreased carotenoid accumulation, severe defect in growth as well as reduction in viability upon ultraviolet (UV) irradiation. Moreover, crosses inducing meiotic silencing of cmd resulted in a barren phenotype, suggesting its role in sexual development in N. crassa. Furthermore, I performed site-directed mutagenesis of the calcium/calmodulin-dependent kinase-2 (Ca2+/CaMK-2) phosphorylation sites corresponding to serine 247 and threonine 267. The camk-2S247A and the camk-2T267A mutants in a homozygous cross, or in a heterozygous cross with a ?camk-2 mutant, showed an intermediate phenotype, indicating requirement of these phosphorylation sites for full fertility. Additionally, fold change expression level of cmd, trm-9, nca-2 and some others related Ca2+ signaling genes using Real-Time PCR indicated a complex interaction pattern among Ca2+-signaling genes. Therefore, this study revealed role of the CaM and related proteins in vegetative and sexual development in N. crassa.
Tamuli, Ranjan
Bora, Utpal
Keywords: BIOSCIENCES AND BIOENGINEERING